Relación del PH Salival con la caries dental en los estudiantes de la Universidad Nacional de Loja, de la Modalidad de estudios presencial en el periodo mayo - julio del 2014. - Guamán Gualán, Nancy Patricia (2014)
KEY WORDS: Dental caries, salivary pH, prevalence, students. The dental caries is one of the most prevalent diseases worldwide, affecting 90% of the population. His appearance was greatly associated with sociocultural, economic, environmental and behavioral factors. The present study takes as targets to determine the relationship of salivary pH with dental caries, to establish the prevalence of dental caries and type of salivary pH in the oral cavity of the students of the National University of Loja, of the form of studies presencial in the period May – July, 2014. Is a descriptive and transversal study, which following the inclusion and exclusion criterion was sampled 873 students aged between 18 and 30 years old; used as an instrument of data collection, the dental history, and to determine the type of salivary pH was used litmus paper, which was placed under the tongue for 15 seconds. The prevalence of dental caries in students was 81%. In relation to the salivary pH showed that 70% were neutral salivary pH, 14% acid pH and 16% basic pH. Was not found a relationship between dental caries and salivary pH, because the predominant pH in the population evaluated was the neutral salivary pH.